JANUARY EFFECT PADA SEKTOR PROPERTY, REAL ESTATE, DAN BUILDING CONSTRUCTION DI BEI - Audina, Mellina; Laturette, Kazia (Program Studi Akuntansi FPEB UPI, 2017)
This research was conducted on property sector, real estate, and building construction sector that are listed in Indonesia’s stock market 2014-2016. This research used quantitive analysis. The purpose of this research was to determine if there is any significant difference between the average abnormal stock return in January and the other months (February to December).. The data used in this research were secondary data. From 56 stocks, 38 stocks were selected as a sample. The sampling method used was purposive sampling. The collected data had been analyzed with Independent sample t-test and the normality data was tested with Saphiro-Wilk test. The result confirmed that there was no January effect in property, real estate, and building construction sector in Indonesia’s stock market 2014-2016.